Pemanfaatan Digital Marketing dalam Pemasaran Produk Para Pelaku UMKM di Daerah Tangerang Selatan - Afridayani Afridayani; Lyandra Aisyah Margie; Yulianto Yulianto (Universitas Pamulang, 2022)
The purpose of this Community Service activity is to carry out one of the Tri Dharma of Higher Education and its main objective is to provide solutions to the problems faced by Micro, Small and Medium Enterprises (MSMEs) actors, especially Pamulang Estate SMEs. In addition, it is hoped that with this community service the existence of higher education institutions can make a major contribution to the development and application of science to the community. The method used in this service is by counseling and training in the form of seminars and also field assistance in order to find solutions to the problems faced by MSME business actors. The results of this community service are in the form of knowledge and understanding of how to create social media accounts, especially market places as an effort to implement digital marketing. The knowledge gained in Community Service is expected to be able to provide new enthusiasm for lecturers in an effort to develop themselves in providing direction, delivering material and motivation and contributing to the development of the business world, especially the MSME sector both around the campus environment and nationally.